Biosafety and biohazard considerations of HSV-1–based oncolytic viral immunotherapy - Robilotti, Elizabeth; Zeitouni, Nathalie C.; Orloff, Marlana (Frontiers in Molecular Biosciences, 2023)
Oncolytic viral immunotherapies are agents which can directly kill tumor cells and activate an immune response. Oncolytic viruses (OVs) range from native/unmodified viruses to genetically modified, attenuated viruses with the capacity to preferentially replicate in and kill tumors, leaving normal tissue unharmed. Talimogene laherparepvec (T-VEC) is the only OV approved for patient use in the United States; however, during the last 20 years, there have been a substantial number of clinical trials using OV immunotherapies across a broad range of cancers. Like T-VEC, many OV immunotherapies in clinical development are based on the herpes simplex virus type 1 (HSV-1), with genetic modifications for tumor selectivity, safety, and immunogenicity. Despite these modifications, HSV-1 OV immunotherapies are often treated with the same biosafety guidelines as the wild-type virus, potentially leading to reduced patient access and logistical hurdles for treatment centers, including community treatment centers and small group or private practices, and healthcare workers. Despite the lack of real-world evidence documenting possible transmission to close contacts, and in the setting of shedding and biodistribution analyses for T-VEC demonstrating limited infectivity and low risk of spread to healthcare workers, barriers to treatment with OV immunotherapies remain. With comprehensive information and educational programs, our hope is that updated biosafety guidance on OV immunotherapies will reduce logistical hurdles to ensure that patients have access to these innovative and potentially life-saving medicines across treatment settings. This work reviews a comprehensive collection of data in conjunction with the opinions of the authors based on their clinical experience to provide the suggested framework and key considerations for implementing biosafety protocols for OV immunotherapies, namely T-VEC, the only approved agent to date.